Practices and perceptions of resistance training load quantification - Moriarty, B.; Watts, D.; Gastin, P.; Weakley, J.; Huyhn, M.; James, L. (International Journal of Sports Physiology and Performance, 2026)
Purpose: The aim of this study was to examine how practitioners currently quantify resistance training (RT), evaluate the perceived effectiveness of popular quantification methods, and identify barriers to quantifying RT load.